Efficacy and safety profile of corticosteroids and non-steroidal anti-inflammatory drugs in COVID-19 management: A narrative review - Seth Kwabena Amponsah; Benjamin Tagoe; Ismaila Adams; Kwasi Agyei Bugyei (Frontiers Media S.A., 2022)
Due to the fact that coronavirus disease 2019 (COVID-19) is still prevalent, and current reports show that some parts of the world have seen increase in incidence, it is relevant that health professionals and scientists know about recent or novel trends, especially drug treatments. Additionally, the safety profiles of these drug treatments need to be documented and shared with the public. Some studies have demonstrated the clinical benefits of non-steroidal anti-inflammatory drugs (NSAIDs) and corticosteroids in COVID-19 treatment. On the contrary, others have also reported that NSAIDs and corticosteroids may worsen symptoms associated with COVID-19. While some researchers have suggested that corticosteroids may be helpful if used in the early stages of COVID-19, there are still some conflicting findings regarding the use of corticosteroids in certain viral infections. Our review suggests that methylprednisolone, dexamethasone, and ibuprofen have therapeutic potential in reducing mortality due to COVID-19 among hospitalized patients. This review also highlights the fact that the use of NSAIDs is not associated with adverse outcomes of COVID-19. In reality, evidence suggests that NSAIDs do not increase the risk of COVID-19 infections. Also, the literature reviewed suggests that corticosteroid treatment in COVID-19 was linked with a decrease in all-cause mortality and disease progression, without increase in adverse events when compared to no corticosteroid treatment.